Augmented Diffuser for Horizontal Axis Marine Current Turbine - Aly Hassan Elbatran; Omar Yaakob; Yasser Ahmed; Firdaus Abdallah (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
The potential of renewable energy sources is enormous as they can make a major contribution to the future of energy needs. The ocean has a great potential to become a practical and predictable energy source compared to other energy resources such as solar, wind, and nuclear. It offers different sources of energy which can be utilized namely wave, tidal, offshore wind, thermal, and tidal current. Among these sources, marine tidal current has major advantages such as higher power availability and predictability. The main objective of this research work is to design and develop a horizontal axis marine current turbine (HAMCT) that suitable for operating within Malaysian ocean, which has low speed current (0.5 – 1 m/s average). A prototype of augmented diffuser 4-bladed HAMCT applying NACA 0014 was proposed in the current study. The turbine model has 0.666 m diameter, and it was designed to produce as much as power from flowing water current. Model was constructed and tested at Marine Technology Center (MTC) in three conditions, namely, free tow testing, ducted tow testing, and ducted diffuser tow testing in order to predict the power and efficiency of the turbine system. The results showed that the application of duct was significant to concentrate the flow and diffuser arrangement was effective when it was placed behind of the rotor in this condition of low water current speed. The maximum efficiency Cp obtained in the current system was 0.58.